Polymeric micro-fluidic channel by hot embossing - Mohammad, Amar Sami; Ali, Mohammad Yeakub (2006)
A microfluidic device contains one or more channels having at least one dimension less than 1 mm. Here, polymeric microfluidic channels are fabricated by two successive steps. At first, master copy or microtool is fabricated by EDM and WEDM; then mass replication of polymer microfluidic channels were done by hot embossing.